Repeated low-velocity impact responses of SiC particle reinforced Al metal-matrix composites. Issue 4 (15th February 2022) - Ekici, Recep; Kosedag, Ertan; Demir, Mert
Abstract: This study aimed to investigate experimentally the repeated low-velocity impact behaviors of SiC reinforced aluminum 6061 metal-matrix composites for different volume fractions and energy levels. In addition, the hardness variations were measured by the Vickers hardness tests from the impacted and impact-free cross-sections of the particle reinforced metal-matrix composites. Low-velocity impact tests were applied to composite samples manufactured by powder metallurgy (in 10, 20, and 30% volume fractions) at two total energy levels (15 and 60 J as single) and in repetitions equal to the sum of these energy levels (5 + 5 + 5 and 20 + 20 + 20 J as repeated). As a result, in increasing the impact number for all volume fractions, the total contact time was shortened and the peak contact force increased, whereas both the permanent central deflection and the absorbed energies reduced. Hence, these variations obtained under repeated impacts (5 + 5 + 5 and 20 + 20 + 20 J) revealed that metal-matrix composites showed a tougher behavior with an increase in the impact numbers from 1st to 3rd, particularly because of the strain hardening effect. Furthermore, an increase in volume fraction from 10 to 30% resulted in an increase in the impact strength under all repeated and single impacts despite changing deformation and damage mechanisms due to increasing the strain hardening effect and particle fractures. The hardness was affected by the volume fraction and increased as the volume fraction increased in both the impacted and impact-free zones. The repeated impact increased the impacted zone hardness more than the single impact for all volume fractions. Additionally, the hardness of the impacted zone under 20 + 20 + 20 J repeated impact was measured as the highest value in the 30% volume fraction. Therefore, metal-matrix composites can behave harder with the strain hardening effect under repeated impacts.